2014
DOI: 10.3389/fnagi.2014.00051
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations in hippocampus of SAMP8 senescent mice and modulation by voluntary physical exercise

Abstract: The senescence-accelerated SAMP8 mouse model displays features of cognitive decline and Alzheimer's disease. With the purpose of identifying potential epigenetic markers involved in aging and neurodegeneration, here we analyzed the expression of 84 mature miRNAs, the expression of histone-acetylation regulatory genes and the global histone acetylation in the hippocampus of 8-month-old SAMP8 mice, using SAMR1 mice as control. We also examined the modulation of these parameters by 8 weeks of voluntary exercise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 69 publications
6
52
0
Order By: Relevance
“…Specifically, histone H4 lysine 12 acetylation alterations causes impaired memory consolidation as well as its restoration reinstates the expression of learning-induced genes and in consequence, cognitive abilities [26]. In accordance to Cosín-Tomás [28], we found that CMS increased HDAC2 protein levels only in SAMR1 females, similarly to SAMP8 control mice, which lead us to hypothesize that acetylated histone protein levels were diminished. This was confirmed evaluating acetylated H3 and H4 protein levels.…”
Section: Discussionsupporting
confidence: 81%
“…Specifically, histone H4 lysine 12 acetylation alterations causes impaired memory consolidation as well as its restoration reinstates the expression of learning-induced genes and in consequence, cognitive abilities [26]. In accordance to Cosín-Tomás [28], we found that CMS increased HDAC2 protein levels only in SAMR1 females, similarly to SAMP8 control mice, which lead us to hypothesize that acetylated histone protein levels were diminished. This was confirmed evaluating acetylated H3 and H4 protein levels.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies showed that differences in cognition and emotional hallmarks correlate with neurodegenerative parameters and epigenetic marks in SAMP8 mice. 61,62 An alterations in cognitive behavior (Morris Water Maze and Novel Object Recognition) and non-cognitive emotional behavior (Elevated Plus Maze, Open Field and Swimming Forced Tests) were found in SAMP8 mice compared to SAMR1 mice as early as 2 months and up to 9 months of age. Differences in the molecular determination of protein levels and gene expression, in addition to ELISA DNA methylation/hydroxymethylation levels and the modification by environmental conditions, demonstrated that epigenetic modulation occurs in SAMP8 mice, both in the hippocampus and cortex, and the repression of DNA transcription of specific genes could be the initial and key step in the molecular stream developed in this strain compared to SAMR1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in CoREST and LSD1 under EE conditions could be the initial and key step related with DNA transcription in the molecular stream developed in this strain by EE, ameliorating cognition and other harmful factors gated to neurodegeneration, described as neuronal loss and apoptosis prevention, downregulated kinase activity, and reduction in OS [54].…”
Section: Samp8mentioning
confidence: 93%